The impact of asymptomatic intracranial atherosclerotic stenosis on the clinical outcomes of patients with single subcortical infarction - Yang, Yi; He, Yue; Xu, Yuhao; Han, Wei; Shao, Yuanwei; Zhao, Tian; Yu, Ming (Frontiers in Medicine, 2023)
Background The presence of parental arterial disease (PAD) is correlated with the outcomes of patients with a single subcortical infarction (SSI). Due to the relatively low incidence of PAD, the predictors of outcomes seem to be limited for SSI patients without PAD. This study aims to investigate the association between asymptomatic intracranial atherosclerotic stenosis (aIAS) and outcomes in patients with SSI and in the subgroup without PAD. Methods Patients with SSI were consecutively enrolled. aIAS referred to a stenosis of ≥50% in intracranial arteries irrelevant to SSI by using magnetic resonance angiography. A poor outcome refers to a modified Ranking Scale >2 points at discharge. Results In total, 298 participants were enrolled. The presence of aIAS could predict a poor outcome for all SSI patients [adjusted relative risk (aRR) = 2.14, 95% confidence interval (CI) = 1.17–3.93, p = 0.014] and in the subgroup without PAD (aRR = 3.12, 95% CI = 1.47–6.62, p = 0.003), but not in the subgroup with PAD. Compared with participants with neither aIAS nor PAD, the risk of a poor outcome increased approximately 2-fold in those with aIAS only (aRR = 2.95, 95% CI = 1.55–5.60, p = 0.001) and in those with concomitant aIAS and PAD (aRR = 3.10, 95% CI = 1.62–5.95, p = 0.001). Conclusion The presence of aIAS is a predictor of a poor outcome in SSI patients, especially in those without PAD.